STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) IN IMPROVING PRIMARY SCHOOL STUDENTS' MATHEMATICS LITERACY - Diputra, Komang Sujendra; Tristiantari, Ni Ketut Desia (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2024)
This research aims to develop a STEM-based mathematics learning design for elementary school students. Therefore, this research is included in research and development. The learning design development process follows the Plomp model, which consists of five stages: 1) the initial investigation phase; 2) the design phase; 3) the construction phase (realization); 4) the test, evaluation and revision phase; and 5) implementation phase. The data was collected through interviews, observation, and essay tests. Interviews are used to identify student and teacher responses to learning design. Observations are carried out during the implementation of learning to monitor the process directly. The essay test is used to measure students' mathematical literacy abilities. Data from interviews and observations were analyzed using qualitative descriptive analysis, while quantitative descriptive analysis was used to describe the average student success and the effectiveness of the learning design. The STEM-based mathematics learning design developed is based on the Project Based Learning learning model, adapted to STEM theories and the needs of elementary school students. This design includes six phases: orientation, strategy construction, application, communication, reflection, and assessment. The results of limited trials show that STEM-based mathematics learning designs are effectively implemented in the classroom and can improve students' abilities in solving mathematical literacy problems according to the PISA dimensions.